2020
DOI: 10.1017/jgc.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction in high school and university students: an evaluation in terms of various psychological, social and personal variables

Abstract: The purpose of this research was to examine internet addiction among high school and university students in terms of interpersonal relationships, automatic thoughts and problem-solving skills. The sample of the study comprised a total of 480 participants: 195 (40.6%) high school and 285 (59.4%) university students. Females constituted 53.3% (256) of the participants and males 46.7% (224). In addition to a Personal Information Form, the Interpersonal Relationship Styles Scale, Automatic Thoughts Scale, Problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For example, the study by Delgado et al [6] involving 1405 university students found that students with better social skills were less likely to be addicted to social networks. Similarly, Odaci et al conducted a study involving 480 students and found that inhibitory interpersonal relationships, automatic thoughts and problem-solving skills are predictors of problematic internet use [15]. Similar conclusions were reached by Terroso and Argimon [8].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…For example, the study by Delgado et al [6] involving 1405 university students found that students with better social skills were less likely to be addicted to social networks. Similarly, Odaci et al conducted a study involving 480 students and found that inhibitory interpersonal relationships, automatic thoughts and problem-solving skills are predictors of problematic internet use [15]. Similar conclusions were reached by Terroso and Argimon [8].…”
Section: Discussionmentioning
confidence: 66%
“…However, on the other hand, there are authors who argue that problematic internet use reduces the time spent on interpersonal relationships and can lead to social isolation [14,15]. Increased time spent on the Internet could lead to a decrease in face-to-face communication and thus a decrease in social interaction [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation